Multiculturalism in Inercultural Tolerant Communication of Innovative Educational Space of Ukrainain Preschool - (:unkn) unknown (INT JOURNAL APPLIED EXERCISE PHYSIOLOGY, 2020)
The article outlines the innovations in preschool education caused by axiological transformations of society. The preschool space of has been defined as the initial basis of education, formed by a combination of social and educational environment. The methodological foundations of the studied problem have been determined and the ontology of the main research concepts has been made. The preschool age is favorable for the tolerance formation as the most sensitive basis for learning values human life priorities. An attempt has been made for the first time to explore the possibilities of using the principle of multiculturalism as an organizational component of tolerant intercultural communication in the educational space of Ukrainian preschool, created within the framework of the updated regulatory and methodological support. The analysis of pre-school child development programs has shown that, despite their regional or state application, they, in the context of the current legal framework, provide a methodological basis for the creation of a local educational space for a preschool institution. The program content filling includes the potential for preschooler's tolerance formation in the context of combination of cultural, linguistic, social and related competences, in accordance with the age-old psychological mechanism of preschool age of child development. The described innovative approach in the organization of tolerant intercultural communication in Ukrainian preschool space can be creatively and practically adapted in the conditions of any modern multicultural society.
Keywords: innovation; intercultural communication; multiculturalism; tolerance; educational space; educational principle; preschool organization